A Cryptic Plant Terpene Cyclase Producing Unconventional 18‐ and 14‐Membered Macrocyclic C25 and C20 Terpenoids with Immunosuppressive Activity. Issue 48 (28th October 2021) - Chen, Yue‐Gui; Li, De‐Sen; Ling, Yi; Liu, Yan‐Chun; Zuo, Zhi‐Li; Gan, Li‐She; Luo, Shi‐Hong; Hua, Juan; Chen, Ding‐Yuan; Xu, Fan; Li, Man; Guo, Kai; et al.
Abstract: A versatile terpene synthase (LcTPS2) producing unconventional macrocyclic terpenoids was characterized from Leucosceptrum canum. Engineered Escherichia coli and Nicotiana benthamiana expressing LcTPS2 produced six 18‐/14‐membered sesterterpenoids including five new ones and two 14‐membered diterpenoids. These products represent the first macrocyclic sesterterpenoids from plants and the largest sesterterpenoid ring system identified to date. Two variants F516A and F516G producing approximately 3.3‐ and 2.5‐fold, respectively, more sesterterpenoids than the wild‐type enzyme were engineered. Both 18‐ and 14‐membered ring sesterterpenoids displayed significant inhibitory activity on the IL‐2 and IFN‐γ production of T cells probably via inhibition of the MAPK pathway. The findings will contribute to the development of efficient biocatalysts to create bioactive macrocyclic sesterterpenoids, and also herald a new potential in the well‐trodden territory of plant terpenoid biosynthesis. Abstract : A cryptic plant terpene cyclase producing unconventional macrocyclic sesterterpenoids and diterpenoids was characterized from Leucosceptrum canum . Two variants producing more sesterterpenoids were engineered, and the immunosuppressive activity of these sesterterpenoids was found.